2014
DOI: 10.1007/s00248-014-0372-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Analysis of Oral Microbiota Shifting in Various Caries States in Childhood

Abstract: Dental caries is one of the most prevalent childhood diseases worldwide, but little is known about the dynamic characteristics of oral microbiota in the development of dental caries. To investigate the shifting bacterial profiles in different caries states, 60 children (3-7-year-old) were enrolled in this study, including 30 caries-free subjects and 30 caries-active subjects. Supragingival plaques were collected from caries-active subjects on intact enamel, white spot lesions and carious dentin lesions. Plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
114
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 49 publications
9
114
0
1
Order By: Relevance
“…A similar result was found in previous studies involving dentine lesions found in children Color version available online [Jiang et al, 2014] and adults [Simón-Soro et al, 2013] without considering lesion activity status. A possible contribution of these micro-organisms to the inactivation of the lesions can be suggested, since several streptococcal species are able to produce alkali [Nascimento and Burne, 2014] that can neutralize acid in disease-associated biofilms and favour an increase in local pH, which is compatible with the high pH of arrested lesions [Hojo et al, 1994;Kuriba yashi et al, 2012].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar result was found in previous studies involving dentine lesions found in children Color version available online [Jiang et al, 2014] and adults [Simón-Soro et al, 2013] without considering lesion activity status. A possible contribution of these micro-organisms to the inactivation of the lesions can be suggested, since several streptococcal species are able to produce alkali [Nascimento and Burne, 2014] that can neutralize acid in disease-associated biofilms and favour an increase in local pH, which is compatible with the high pH of arrested lesions [Hojo et al, 1994;Kuriba yashi et al, 2012].…”
Section: Discussionsupporting
confidence: 77%
“…The polymicrobial nature of caries has been well established [Simón-Soro et al, 2013Jiang et al, 2014], and S. mutans is an oral bacterium that can contribute to the onset and progression of caries [Mattos-Graner et al, 2001;Nobre-dos-Santos et al, 2002;Aas et al, 2008;Takahashi and Nyvad, 2008;Palmer et al, 2010;Bowen and Koo, 2011;Luo et al, 2012]. The cariogenic potential of S. mutans is mainly attributed to its capacity to: (i) form biofilms on the tooth surfaces, (ii) produce weak acids, mainly lactic acid, and (iii) adapt to environmental stress conditions such as fluctuations in pH, oxygen tension and nutrient availability [Lemos and Burne, 2008].…”
mentioning
confidence: 99%
“…Of interest, different bacterial profiles were observed depending on the stage of caries development, and a reduced bacterial diversity was observed in the microbiota of advanced dentin lesions [62]. These data support the 'ecological plaque hypothesis' [63] which states that caries is a result of a shift in the homeostatic balance of the resident microbiota due to local environmental changes which will favor the outgrowth of more cariogenic species initially present in low numbers.…”
Section: Cariogenic Biofilmsupporting
confidence: 70%
“…1). The latter two genera have been found in elevated levels in dentin lesions [38,39] and have also been associated with periodontal disease [40].…”
Section: Discussionmentioning
confidence: 99%